Temperature controlled microcapsule loaded with Perilla essential oil and its application in preservation of peaches - Tai, Zhigang; Zheng, Minjie; Yang, Ye; Xie, Cheng; Li, Zhenjie; Xu, Chunping (Frontiers in Nutrition, 2023)
In this study, Perilla frutescens essential oil (PEO) loaded microcapsules (PEOM) were successfully prepared and their thermal stability, temperature-responsive releasing effect, antioxidant activity, anti-bacterial activity, and preservation of peach were systematically investigated. PEOM showed excellent encapsulation efficiency (91.5%) with a core-shell ratio of 1.4:1 and exhibited high thermal stability, indicating that PEOM could effectively maintain PEO release rate. In vitro assays indicated that the optimal kinetic model for PEO release fitted well with first order with a diffusion mechanism. A high level of antioxidant and antibaterial activity of PEOM was maintained. In addition, owing to its sustained release, PEOM could prolong the shelf life of peaches significantly. Therefore, PEOM has potential application and development prospects in the field of food preservation.